STABILITAS DAN AKTIVITAS GEL EKSTRAK BULBUS BAWANG TIWAI (Eleutherine americana (Mill.) Urb.) SEBAGAI ANTI ACNE - Husnul Warnida; Yullia Sukawaty; Mega Mega (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
awang Tiwai has an antibacterial activity toward some microorganisms e.g. Staphylococcus epidermidis dan Propionibacterium acne, two acne related bacteria. Bawang Tiwai extract 1% and 2% were formulated into gel (no oil content, because oil could make the acne worse) with carbomer 940 as gelling agent. Physical stability of bawang tiwai gel was evaluated included stability, organoleptic, pH, homogeneity, viscosity, consistency, spreading test, and activity toward Staphylococcus epidermidis. The result showed that all formulas are stable after 7 days. The test results of antibacterial activity gel are 17,24 mm dan gel 19,75 mm to gel 1% dan 2% respectively.